Clinical onset and course, response to treatment and outcome in 24 patients with the cblE or cblG remethylation defect complemented by genetic and in vitro enzyme study data. Issue 5 (20th December 2014) - Huemer, M.; Bürer, C.; Ješina, P.; Kožich, V.; Landolt, M. A.; Suormala, T.; Fowler, B.; Augoustides‐ Savvopoulou, P.; Blair, E.; Brennerova, K.; Broomfield, A.; De Meirleir, L.; et al.
Abstract: Background: The cobalamin E (cblE) (MTRR, methionine synthase reductase) and cobalamin G (cblG) (MTR, methionine synthase) defects are rare inborn errors of cobalamin metabolism leading to impairment of the remethylation of homocysteine to methionine. Methods: Information on clinical and laboratory data at initial full assessment and during the course of the disease, treatment, outcome and quality of life was obtained in a survey‐based, retrospective study from physicians caring for patients with the CblE or CblG defect. In addition, data on enzyme studies in cultured skin fibroblasts and mutations in the MTRR and MTR gene were analysed. Results: In 11 cblE and 13 cblG patients, failure to thrive, feeding problems, delayed milestones, muscular hypotonia, cognitive impairment and macrocytic anaemia were the most frequent symptoms. Delay in diagnosis depended on age at first symptom and clinical pattern at presentation and correlated significantly with impaired communication abilities at follow‐up. Eighteen/22 patients presented with brain atrophy or white matter disease. Biochemical response to treatment with variable combinations of betaine, cobalamin, folate was significant. The overall course was considered improving ( n = 8) or stable ( n = 15) in 96 % of patients, however the average number of CNS symptoms per patient increased significantly over time and 16 of 23 patients were classified as developmentally delayed or severely handicapped. In vitro enzyme analysis data showed no correlation with outcome. Predominantly private mutations were detected and no genotype– phenotype correlations evident. Conclusions: The majority of patients with the cblE and cblG defect show limited clinical response to treatment and have neurocognitive impairment.